2018
DOI: 10.1016/j.mex.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the information obtained from chamber-based greenhouse gas exchange measurements in remote areas

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Independent correction schemes have also been developed (Tirol‐Padre et al., 2014; van der Weerden, Clough, & Styles, 2013). Field study has shown that care is needed to get useful quantitative data (Debouk et al., 2018; Nicoloso et al., 2013) The instruments are also sensitive to environmental temperature (Debouk et al., 2018; Rosenstock et al., 2013) and other instrument drifts (Palzer, 2020). Providing that care is taken with deployment, analyzer costs are lower than with many other optical instruments, and portability is good compared with cavity laser spectroscopy.…”
Section: Analysis By Optical and Other Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent correction schemes have also been developed (Tirol‐Padre et al., 2014; van der Weerden, Clough, & Styles, 2013). Field study has shown that care is needed to get useful quantitative data (Debouk et al., 2018; Nicoloso et al., 2013) The instruments are also sensitive to environmental temperature (Debouk et al., 2018; Rosenstock et al., 2013) and other instrument drifts (Palzer, 2020). Providing that care is taken with deployment, analyzer costs are lower than with many other optical instruments, and portability is good compared with cavity laser spectroscopy.…”
Section: Analysis By Optical and Other Detectorsmentioning
confidence: 99%
“…An increasing variety of N 2 O detectors are available for determining concentrations, either directly in the field in online automatic systems (Grace et al., 2020) or from laboratory analysis of chamber headspace samples stored as described above. A third approach, directed towards maximizing data from campaigns in remote or hill country regions, has been to use manual chambers with a portable field analyzer (Debouk, Altimir, & Sebastià, 2018). This approach is likely to become more common when more portable high‐precision N 2 O analyzers become available.…”
Section: Analytical Systems and Detector Optionsmentioning
confidence: 99%
“…In the case of CH4 and N2O we did not detect significant differences among measuring conditions. Therefore, we present the average value considering all three measuring conditions [32].…”
Section: Greenhouse Gas Exchange (Ghg) Measurementsmentioning
confidence: 99%
“…Flux measurements, flux calculation and data quality checks were done according to Debouk et al (2018), including a fitting goodness assessment based on the RAdj 2 value, and filtering fluxes below detection limit, calculated as the standard deviation of the ambient concentration over the measuring time. Negative values refer to the flux from the atmosphere to the biosphere and positive values correspond to the flux from the biosphere to the atmosphere, according to the micrometeorological sign convention [33].…”
Section: Greenhouse Gas Exchange (Ghg) Measurementsmentioning
confidence: 99%
“…Besides increasing the statistical power [13] and avoiding the negative effects of long chamber closure time on gas diffusion and microclimate [14,15], this would address the observed high spatial heterogeneity and variability of soil properties in the floodplain [16]. A dynamic closed chamber system that is connected to a portable photoacoustic multi-gas monitor [17,18] meets these requirements and had previously shown its suitability for soil emission measurements in remote areas [19][20][21]. However, the accuracy and precision of (particularly N 2 O) measurements made by the photoacoustic monitor were the subject of earlier discussions [22,23] and should be considered during the interpretation of study results.…”
Section: Introductionmentioning
confidence: 99%